Comparative Study of the Ijtihad Method of the Indonesian Ulema Council and Bahtsul Masail Nahdlatul Ulama on the Fatwa of the Astrazeneca Vaccine
This paper aims to compare the ijtihad methods used by the Indonesian Council of Ulema (MUI) and Bahtsul Masail Nahdlatul Ulama concerning the fatwa on the AstraZeneca COVID-19 vaccine. The study method is qualitative, with a normative legal approach and descriptive-comparative analysis. According to the findings of this study, MUI employs the type of ijtihad jama>’iy (collective ijtihad) and interdisciplinary by using ijtihad baya>ni, ta'lili, and istis